2013
DOI: 10.2169/internalmedicine.52.0697
|View full text |Cite
|
Sign up to set email alerts
|

Severe Lactic Acidosis and Acute Pancreatitis Associated with Cimetidine in a Patient with Type 2 Diabetes Mellitus Taking Metformin

Abstract: An 82-year-old woman with type 2 diabetes mellitus, hypertension, and unstable angina presented with severe lactic acidosis and acute kidney injury (AKI) accompanied by acute pancreatitis. Her medical history revealed that she had taken cimetidine for two weeks while taking other medications, including metformin. Continuous veno-venous hemodiafiltration (CVVHDF) was initiated under diagnosis of lactic acidosis due to metformin and AKI caused by cimetidine-induced acute pancreatitis. In three days of CVVHDF, th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2013
2013
2020
2020

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(3 citation statements)
references
References 13 publications
(11 reference statements)
0
3
0
Order By: Relevance
“…Thus, the risk of AP due to the suspected drug is more easily discerned through the confounding factors and often is different from that gleaned from case report data. For example, an association between oral hypoglycemics and AP has been speculated based upon numerous published case reports [73][74][75]126,159,[287][288][289][290][427][428][429][430][431]491,506,604]; however, systematic review and/or meta-analysis of trial data have demonstrated no association with AP for vildagliptin alone [612] or for dipeptidyl peptidase-4 inhibitors (DPP4i) as a group (i.e., vildagliptin, sitagliptin, saxagliptin, alogliptin, linagliptin, and dutogliptin) [613]. Another systematic review of various study designs concluded that AP during oral hypoglycemic therapy was a rare event and that if an association exists, it is not as strong as originally thought [614].…”
Section: Discussionmentioning
confidence: 99%
“…Thus, the risk of AP due to the suspected drug is more easily discerned through the confounding factors and often is different from that gleaned from case report data. For example, an association between oral hypoglycemics and AP has been speculated based upon numerous published case reports [73][74][75]126,159,[287][288][289][290][427][428][429][430][431]491,506,604]; however, systematic review and/or meta-analysis of trial data have demonstrated no association with AP for vildagliptin alone [612] or for dipeptidyl peptidase-4 inhibitors (DPP4i) as a group (i.e., vildagliptin, sitagliptin, saxagliptin, alogliptin, linagliptin, and dutogliptin) [613]. Another systematic review of various study designs concluded that AP during oral hypoglycemic therapy was a rare event and that if an association exists, it is not as strong as originally thought [614].…”
Section: Discussionmentioning
confidence: 99%
“…Overall, 20.7% of these patients died; four patients died from multiorgan failure (three from acetaminophen and erlotinib), and two died from an infection (sulfamethoxazole-trimethoprim and cimetidine). 27,38,106,112,115 The medication implicated in causing the drug-induced disease was permanently discontinued or not reported in 27 (93.1%) and 2 (6.9%) cases, respectively. The drug-induced disease should be managed with the appropriate supportive care and disease-state specific targeted therapies.…”
Section: Discussionmentioning
confidence: 99%
“… 17 , 18 Concomitant use of Metformin and Cimetidine decrease the excretion of Metformin, resulting in increased exposure of Metformin and elevated risk of Metformin Associated Lactic Acidosis (MALA). 19 , 20 It is recommended to reduce the dose of Metformin when Cimetidine is co-prescribed. 21 …”
Section: Interactions With Acid Suppressing Agentsmentioning
confidence: 99%